Diverse etiologies, diagnostic approach, and management of primary adrenal insufficiency in pediatric age - Han-Wook Yoo (Korean Society of Pediatric Endocrinology, 2021)
Primary adrenal insufficiency (PAI) in pediatric age is a rare, but potentially fatal condition caused by diverse etiologies including biochemical defects of steroid biosynthesis, developmental abnormalities of the adrenal gland, or reduced responsiveness to adrenocorticotropic hormone. Compared to adult PAI, pediatric PAI is more often the result of genetic (monogenic, syndromic disorders) than acquired conditions. During the past decade, rare monogenic disorders associated with PAI have helped unravel the underlying novel molecular genetic mechanism. The diagnosis of adrenal insufficiency in children and young infancy is often challenging, usually based on clinical suspicion and endocrine laboratory findings. Pediatric endocrinologists sometimes encounter therapeutic difficulty in finding the balance between undertreatment and overtreatment, determining how to optimize the dose over the patient's lifetime, and maximizing mimicry of normal cortisol secretion with glucocorticoid replacement therapy.